Adapting Motivational Interventions for Comorbid Schizophrenia and Alcohol Use Disorders - Carey, Kate B. (2007)
The co-occurrence of schizophrenia and alcohol use disorders often leads to poor treatment retention and adherence. Both empirical research and statements of best practices suggest that interventions including motivational interviewing principles can enhance treatment engagement and improve outcomes. This article describes a set of exercises used within a motivational enhancement protocol for outpatients with schizophrenia-spectrum and alcohol use disorders. We describe how each exercise was tailored to the target population, and how it is designed to enhance motivation to change and treatment engagement. Examples from clinical transcripts are used to demonstrate how motivational interviewing is adapted to the cognitive, social, and environmental circumstances associated with schizophrenia.